Current overview of COVID-19 vaccination process in Serbia - Catić-Đorđević, Aleksandra; Stefanović, Nikola; Spasić , Ana; Damnjanović, Ivana; Veličković-Radovanović, Radmila; Đinđić, Boris; Pavlović, Dragana (Acta medicae Medianae, 2021)
It has been more than a year since the beginning of the coronavirus disease 2019 (COVID-19) pandemic caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2). As a result of collaborations of worldwide researchers, four COVID-19 vaccines of different manufacturers and types are available in Serbia since December 2020, and citizens can choose one of them. Mild to moderate adverse effects are expected and usually resolve within one day after vaccination.This study aimed to make a current overview of the vaccination process in Serbia as a cross-section of attitudes and adverse effects related to the COVID-19 vaccines during the period of mass vaccination.The data collected via the online survey platform. The participants were invited to voluntarily complete an online questionnaire in their native language from the beginning of March to April 12, 2021.The conducted research included 573 respondents who filled out the questionnaire: 174 (30.37%) men and 399 (69.63%) women, with an average age of 43.55±13.17 years. The largest number of respondents received Pfizer/BioNTech (40.14%) or Sinopharm vaccine (42.93%). Pfizer/BioNTech vaccine prevalence was higher among male respondents, healthcare professionals, and the younger population. The most common local adverse effect included pain or tenderness at the injection site. Fever, muscle/joint pain, and tiredness were reported as the most common systemic adverse effects, especially after the second dose of vaccines.The vaccination process in Serbia started quickly and is persisting with high intensity. A widespread vaccination process can lead to pandemic control and a reduction in SARS-CoV-2-induced death.
Keywords: pandemic, COVID-19, SARS-CoV-2, vaccination